Shape Notes, Gospels and Spirituals: Rediscovering Spirituality in the 21st Century (American & British Studies Annual, 2008)
Spirituals, gospels and Sacred harp songs (recorded on paper with the help of specific form of shape notes) represent a strong 19th century American cultural tradition. Their lyrics contributed to the originality of the independent American literature. In the 20th century, these songs left Church environment and made themselves at home in popular culture too. In the Czech lands, their acceptance was given mainly thanks to the strong rhythm and emotional performance. The Czech Republic is a post-communist country with the highest percentage of atheists. Despite that, Czechs like sacred music, especially American spirituals and gospels. In the following lines I would like to show where modern roots and limits of this interest are and what challenges the Czechs have had in facing the perception of American sacred music after 1989.
Keywords: American music; gospel; spirituals; Sacred harp songs; shape notes; perception of American sacred music